Resistance Training with Single vs. Multi-joint Exercises at Equal Total Load Volume: Effects on Body Composition, Cardiorespiratory Fitness, and Muscle Strength - Paoli, Antonio; Gentil, Paulo; Moro, Tatiana; Marcolin, Giuseppe; Bianco, Antonino (Frontiers in Physiology, 2017)
The present study aimed to compare the effects of equal-volume resistance training performed with single-joint (SJ) or multi-joint exercises (MJ) on VO2max, muscle strength and body composition in physically active males. Thirty-six participants were divided in two groups: SJ group (n=18, 182.1±5.2, 80.03±2.78kg, 23.5±2.7yrs) exercised with only SJ exercises (e.g. dumbbell flying, knee extensions etc.) and MJ group (n=18, 185.3±3.6cm, 80.69±2.98kg, 25.5±3.8yrs) with only MJ exercises (e.g. bench press, squat, etc.). The total work volume (repetitions x sets x load) was equated between groups. Training was performed three times a week for 8 weeks. Before and after the training period, participants were tested for VO2max, body composition, 1 RM on the bench press, leg extension and squat. Analysis of covariance (ANCOVA) was used to compare post training values between groups, using baseline values as covariates. According to the results, both groups decreased body fat and increase fat free mass with no difference between them. Whilst both groups significantly increased cardiorespiratory fitness and maximal strength, the improvements in MJ group were higher than for SJ in VO2max (5.1% and 12.5% for SJ and MJ), bench press 1RM (8.1% and 10.9% for SJ and MJ), leg extension 1RM (12.4% and 18.9% for SJ and MJ) and squat 1RM (8.3% and 13.8% for SJ and MJ). In conclusion, when total work volume was equated, RT programs involving MJ exercises appears to be more efficient in improving muscle strength and maximal oxygen consumption than programs involving SJ exercises, but no differences were found for body composition.